Keabsahan Pembangunan Rumah Susun Umum Gunung Anyar di atas Tanah Terindikasi Terlantar oleh Pemerintah Kota Surabaya - Haninah (Magister Kenotariatan Universitas Surabaya, 2024)
Indonesia is a developing country which is one of the most populous countries in the world, so to overcome the rapid population growth, especially for low income communities, the government is building public flats to help people get a place to live. This also happened in the city of Surabaya, as one of the big cities in Indonesia, where the Surabaya City government built public flats, one of which was in the Gunung Anyar area for the surrounding community. This research aims to examine the legality of the construction of the Gunung Anyar public flats which the Surabaya City Government recognizes as being built on land indicated as abandoned land. This research is normative juridical research with a conceptual and statutory approach. The research results concluded that the legality of the construction of the Gunung Anyar public flats was questionable or invalid considering that the land used by the government to build the flats was not properly qualified as abandoned land based on existing legal provisions. Apart from that, there is no clarity regarding the procedures for determining abandoned land carried out by the government in accordance with existing legal provisions.